If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 = -2(v + -8) Reorder the terms: 42 = -2(-8 + v) 42 = (-8 * -2 + v * -2) 42 = (16 + -2v) Solving 42 = 16 + -2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '2v' to each side of the equation. 42 + 2v = 16 + -2v + 2v Combine like terms: -2v + 2v = 0 42 + 2v = 16 + 0 42 + 2v = 16 Add '-42' to each side of the equation. 42 + -42 + 2v = 16 + -42 Combine like terms: 42 + -42 = 0 0 + 2v = 16 + -42 2v = 16 + -42 Combine like terms: 16 + -42 = -26 2v = -26 Divide each side by '2'. v = -13 Simplifying v = -13
| 7+0=x | | -21=9d-7d | | 220=g+70 | | 5(c-6)c+11=24 | | -12=6(x+7) | | 7+y+12y=7 | | -8n+2=-3n-3 | | -5p-24=21(-1+3p) | | b+3-9=29 | | 4(-3+v)=36 | | f(5)=4x-3 | | -5(2s+2m)= | | -111=-3(1+6n) | | 50+5x=15+12x | | 12x-5=4x-1 | | 7x+11=7+7x | | -2(-4+y)-5y=15 | | -13+4b=-3b-7 | | 4x-3+2x+53=90 | | y=5x^2+2x-1 | | -3(g-9)+-9=-9 | | 4x-3+2x+53=180 | | 3x+x-2=-x+7 | | 2(p-4)-3=9 | | 5x+5(2x+11)=160 | | 2=k+2+5k | | 12+-5=x | | 6b-7b=13 | | x^5+2x^4-5x^3-10x^2+4x+8=0 | | N+19=12 | | -(c-4)=1 | | 106+4d=40 |